Penerapan Metode Algoritma A* Untuk Penentuan Jalur Terpendek Dalam Pengiriman Barang Berbasis Mobile - Syafrial Nursaily; Hairul Agustian (TeknoIS : Jurnal Ilmiah Teknologi Informasi dan Sains, 2023)
PT. Pos Indonesia is a Regional Owned Enterprise whose aim is to participate in implementing and supporting government policies and programs in the field of economy and national development, especially in the field of postal and giro services to the public. The current services is no longer only focused on mail services but has opened various domestic and nondomestic (overseas) delivery services. In shipping services, there are several obstacles that must be faced including the condition of the roads being traversed and congestion. Several road conditions were inadequate, ranging from damaged roads, closed roads, to roads that were impassable for large trucks, trailers, and wing boxes. These obstacles will certainly increase of operational costs and even delays in delivering goods to their destination, which will reduce the level of service to customers. To reduce operational costs and improve service to customers, of course, the innovation is needed. One of them, is to adjust the distance for the delivery of goods according to the location and conditions of the delivery area by create a mobile which based on application by applying the A* algorithm method which is represented in the form of a graph or image.